Aerobic Exercise Inhibited P2X7 Purinergic Receptors to Improve Cardiac Remodeling in Mice With Type 2 Diabetes - Wang, Ting; Li, Jianmin; Li, Hui; Zhong, Xin; Wang, Luya; Zhao, Shujue; Liu, Xuesheng; Huang, Zhouqing; Wang, Yonghua (Frontiers in Physiology, 2022)
Background: Diabetic cardiomyopathy (DCM), the main complication of diabetes mellitus, presents as cardiac dysfunction by ventricular remodeling. In addition, the inhibition of P2X7 purinergic receptors (P2X7R) alleviates cardiac fibrosis and apoptosis in Type 1 diatebes. However, whether exercise training improves cardiac remodeling by regulating P2X7R remains unknown. Methods: Db/db mice spontaneously induced with type 2 diabetes and high-fat diet (HFD) and mice with streptozotin (STZ)-induced type 2 diabetes mice were treated by 12-week treadmill training. Cardiac functions were observed by two-dimensional echocardiography. Hematoxylin-eosin staining, Sirius red staining and transmission electron microscopy were respectively used to detect cardiac morphology, fibrosis and mitochondria. In addidion, real-time polymerase chain reaction and Western Blot were used to detect mRNA and protein levels. Results: Studying the hearts of db/db mice and STZ-induced mice, we found that collagen deposition and the number of disordered cells signiﬁcantly increased compared with the control group. However, exercise markedly reversed these changes, and the same tendency was observed in the expression of MMP9, COL-I, and TGF-β, which indicated cardiac fibrotic and hypertrophic markers, including ANP and MyHC expression. In addition, the increased Caspase-3 level and the ratio of Bax/Bcl2 were reduced by exercise training, and similar results were observed in the TUNEL test. Notably, the expression of P2X7R was greatly upregulated in the hearts of db/db mice and HFD+STZ-induced DM mice and downregulated by aerobic exercise. Moreover, we indicated that P2X7R knock out signiﬁcantly reduced the collagen deposition and disordered cells in the DM group. Furthermore, the apoptosis levels and TUNEL analysis were greatly inhibited by exercise or in the P2X7R-/- group in DM. We found significant differences between the P2X7R-/-+DM+EX group and DM+EX group in myocardial tissue apoptosis and fibrosis, in which the former is significantly milder. Moreover, compared with the P2X7R-/-+DM group, the P2X7R-/-+DM+EX group represented a lower level of cardiac fibrosis. The expression levels of TGF-β at the protein level and TGF-β and ANP at the genetic level were evidently decreased in the P2X7R-/-+DM+EX group. Conclusion: Aerobic exercise reversed cardiac remodeling in diabetic mice at least partly through inhibiting P2X7R expression in cardiomyocytes.